1972
DOI: 10.1039/c39720000451
|View full text |Cite
|
Sign up to set email alerts
|

The photochemistry of flavanone

Abstract: On U.V. irradiation, flavanone rearranges to undergoes fragmentation to yield a highly reactive 4-phenyldihydrocoumarin and 2'-hydroxychalcone, and keto-keten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1972
1972
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Mack and Pinhey [ 60 ] transformed flavanone 68 , via fragmentation of the heterocyclic benzylic O-C bond, into 2'-hydroxychalcone 70 (20%) in benzene at 250 nm. They also isolated salicylic acid ( 73 , 4%) via the subsequent fragmentation of the C2-C3 bond to form a ketene 72 that can be trapped with water or methanol.…”
Section: Chalcone and Flavanone Photochemistrymentioning
confidence: 99%
“…Mack and Pinhey [ 60 ] transformed flavanone 68 , via fragmentation of the heterocyclic benzylic O-C bond, into 2'-hydroxychalcone 70 (20%) in benzene at 250 nm. They also isolated salicylic acid ( 73 , 4%) via the subsequent fragmentation of the C2-C3 bond to form a ketene 72 that can be trapped with water or methanol.…”
Section: Chalcone and Flavanone Photochemistrymentioning
confidence: 99%
“…In addition, a number of reports dealing with the aromatization of arene oxides (22) to 4-indanols (24) have shown that these reactions proceed via a spiroketone (23) intermediate. [39][40][41][42] These reports suggested that a related rearrangement might also occur upon irradiation of the chroman ring (25). In order to test for this possibility, we investigated the photochemical behavior of several substituted chromans.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting yellow solution was stirred for 15 min at 0 °C and then 200 mg of methyl iodide was added. The solution was allowed to warm to room temperature and then stirred at 25 °C for 2 h. The reaction mixture was diluted with ether and washed with water. The ethereal layer was dried over magnesium sulfate and concentrated under reduced pressure to give 206 mg (92%) of 3-methyl-3-phenyl-2-benzofuranone: IR (neat) 5.53, 6.18, 6.24, 6.85, 8.12, 9.67,11.20,13.26, and 14.37 µ ; NMR ICDCI3, 60 MHz) r 8.18 (s, 3 H) and 2.9-2.6 (m, 9 H).…”
Section: Methodsmentioning
confidence: 99%
“…On irradiation in benzene some other minor products were detected (t.l.c. ), perhaps (8) and (9) * or derivatives.…”
Section: Materials and Procedures-flavanones'mentioning
confidence: 99%